2021
DOI: 10.1371/journal.pone.0252028
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in suicide-related communication of young suicide victims

Abstract: Objectives There is limited insight into gender differences in suicide-related communication (SRC) in youths. SRC is defined as “the act of conveying one’s own suicide ideation, intent or behaviours to another person”. Increasing our understanding of SRC in youths will enable us to recognize and specify needs of female versus male youths. The current study explores SRC in a sample of Dutch suicide victims aged under 20 and examines gender differences. Methods Interview data from a psychological autopsy study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
(70 reference statements)
1
7
0
8
Order By: Relevance
“…A higher acceptance rate was found on Instagram among adolescents for distress expression, owing to its advanced privacy settings [ 58 ]. The gender differences identified were in line with what was found in the majority of previous studies [ 59 , 60 ]. Interestingly, students from Band 1 schools used Close Friends more often, which contradicted the findings of most prior studies, where social media usage had little or a negative association with academic performance [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…A higher acceptance rate was found on Instagram among adolescents for distress expression, owing to its advanced privacy settings [ 58 ]. The gender differences identified were in line with what was found in the majority of previous studies [ 59 , 60 ]. Interestingly, students from Band 1 schools used Close Friends more often, which contradicted the findings of most prior studies, where social media usage had little or a negative association with academic performance [ 61 , 62 ].…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review and meta-analysis of randomized controlled trials (RCTs) found self-guided digital interventions are effective for directly targeting individuals’ suicidal ideation (immediately after post-intervention) ( Torok et al, 2020 ). An emerging indication of a late debut and ambiguous presentation of suicide-related communication in boys led to the suggestion for future research to explore online suicide-related communication and the potential for suicide prevention on digital platforms ( Balt et al, 2021 ). To our knowledge, there is no literature specifically focusing on gender differences in the efficacy of digital assistance in suicide prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Those young men communicate at a later stage and less clearly than young women who died by suicide. Compared to girls, SRC by boys was more ambiguous or diluted by "humorous" connotations [32].…”
Section: Introductionmentioning
confidence: 88%
“…It was difficult for recipients to assess the intent, meaning and relevance of the statements [30,31]. Balt et al [32] address gender differences in SRC. Again, these data relate to a psychological autopsy study and interviews with relatives of young men and women who have died by suicide.…”
Section: Introductionmentioning
confidence: 99%